Personality, social factors, brain functioning, familial risk, and trajectories of alcohol misuse in adolescence - Tschorn, Mira; Daedelow, Laura; Szalek, Laura; Banaschewski, Tobias; Bokde, Arun L. W.; Desrivières, Sylvane; Flor, Herta; Grigis, Antoine; Garavan, Hugh; Gowland, Penny; Martinot, Jean-Luc; Martinot, Marie-Laure Paillère; et al. (JAMA network open, 2024)
The development of an alcohol use disorder in adolescence is associated with increased risk of future alcohol dependence. The differential associations of risk factors with alcohol use over the course of 8 years are important for preventive measures.To determine the differential associations of risk-taking aspects of personality, social factors, brain functioning, and familial risk with hazardous alcohol use in adolescents over the course of 8 years.The IMAGEN multicenter longitudinal cohort study included adolescents recruited from European schools in Germany, the UK, France, and Ireland from January 2008 to January 2019. Eligible participants included those with available neuropsychological, self-report, imaging, and genetic data at baseline. Adolescents who were ineligible for magnetic resonance imaging or had serious medical conditions were excluded. Data analysis was conducted from July 2021 to September 2022.Personality testing, psychosocial factors, brain functioning, and familial risk of alcohol misuse.Hazardous alcohol use as measured with the Alcohol Use Disorders Identification Test scores, a main planned outcome of the IMAGEN study. Alcohol misuse trajectories at ages 14, 16, 19, and 22 years were modeled using latent growth curve models.A total of 2240 adolescents (1110 female [49.6%] and 1130 male [50.4%]) were included in the study. There was a significant negative association of psychosocial resources (β = −0.29; SE = 0.03; P < .001) with the general risk of alcohol misuse as well as a significant positive association of the risk-taking aspects of personality with the intercept (β = 0.19; SE = 0.04; P < .001). Furthermore, there were significant positive associations of the social domain (β = 0.13; SE = 0.02; P < .001) and the personality domain (β = 0.07; SE = 0.02; P < .001) with trajectories of alcohol misuse development over time (slope). Family history of substance misuse was negatively associated with general risk of alcohol misuse (β = −0.04; SE = 0.02; P = .045) and its development over time (β = −0.03; SE = 0.01; P = .01). Brain functioning showed no significant association with intercept or slope of alcohol misuse in the model.The findings of this cohort study suggest known risk factors of adolescent drinking may contribute differentially to future alcohol misuse. This approach may inform more individualized preventive interventions.
Gesehen am 12.11.2024